Patients' experiences and perceptions of Guillain-Barré syndrome: A systematic review and meta-synthesis of qualitative research. - Despina Laparidou; Ffion Curtis; Joseph Akanuwe; Jennifer Jackson; Timothy L Hodgson; A Niroshan Siriwardena (PLoS ONE, 2021)
Background Guillain-Barré syndrome (GBS) is an immune-mediated polyradiculoneuropathy, with an incidence of 1-2/100,000 per year. Its severity is variable, ranging from very mild cases with brief weakness to severe paralysis, leading to inability to breathe independently, or even death. Currently there is limited evidence exploring the experiences of GBS patients. The aim of this study was to review patients' experiences and perceptions of GBS and its variants at diagnosis, discharge and during recovery, by conducting a systematic review and thematic meta-synthesis of qualitative studies of patients' experiences of GBS (and its variants). Methods We searched twelve electronic databases, supplemented with internet searches and forward and backward citation tracking from the included studies and review articles. Data were synthesised thematically following the Thomas and Harden approach. The CASP Qualitative Checklist was used to assess the quality of the included studies of this review. Results Our search strategy identified a total of 5,282 citations and after removing duplicates and excluding citations based on title and abstract, and full-text screening, five studies were included in the review and meta-synthesis; all included studies were considered of acceptable quality. Through constant discussions and an iterative approach, we developed six analytical themes following a patient's journey from suspecting that they had a health problem, through to being hospitalised, experiencing ongoing difficulties, slowly recovering from GBS, adjusting to their new circumstances, and re-evaluating their lives. Conclusions Despite the variety of experiences, it was evident from all included studies that being diagnosed with and surviving GBS was a life-changing experience for all participants. Trial registration Protocol was registered (CRD42019122199) on the International Prospective Register of Systematic Reviews (http://www.crd.york.ac.uk/PROSPERO).